2013
DOI: 10.3324/haematol.2013.086496
|View full text |Cite
|
Sign up to set email alerts
|

No association between the XPD Lys751Gln (rs13181) polymorphism and disease phenotype or leukemic transformation in primary myelofibrosis

Abstract: Philadelphia negative (Ph -) classical myeloproliferative neoplasms (MPNs), i.e. polycythemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis (PMF), are clonal disorders of hematopoiesis with high frequency of recurrent somatic gene mutations, like JAK2V617F and MPLW515L, DNA copy variations, and chromosomal aberrations.1,2 Consequently, the neoplastic process is thought to be initiated, maintained, and enhanced by acquired molecular lesions. However, germ-line variants, like the 46/1 hapl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Exposure to cytoreductive treatments, patient age, and leukocytosis at diagnosis are considered risk factors for progression to acute leukemia in patients with PV and ET [ 60 ]. In contrast, the research conducted by Poletto et al which included 456 Italian MFP patients did not report any association between XPD 2251A>C and the risk of leukemic transformation [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to cytoreductive treatments, patient age, and leukocytosis at diagnosis are considered risk factors for progression to acute leukemia in patients with PV and ET [ 60 ]. In contrast, the research conducted by Poletto et al which included 456 Italian MFP patients did not report any association between XPD 2251A>C and the risk of leukemic transformation [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a change at codon 751 in exon 23 from lysine to glutamine [ 30 ]. XPD 2251A>C polymorphism contributes to hematological neoplasms, such as chronic myeloid leukemia (CML) [ 32 , 33 ], AML [ 29 ], and AML transformation [ 26 ], and some showed no association [ 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inherited variations in DNA‐repair efficiency have been implicated in the predisposition to de novo and therapy‐related AML . Moreover, Hernandez‐Boluda et al identified rs13181 in ERCC2 as an independent risk factor for leukemic transformation in primary myelofibrosis, even though their finding is not without controversy . Several reports linked polymorphisms in the ERCC2 gene with enhanced risk of childhood ALL , although negative results were also reported .…”
Section: Discussionmentioning
confidence: 99%